DETERMINAN : KINERJA KARYAWAN PADA PT ASURANSI JIWA BCA (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2021)
ABSTRACTThis study aims to examine the influence of work motivation and work environment on employee performance at PT BCA Life Insurance (BCA Life) Mangga Besar, Central Jakarta with a population of 300 people and a sample of 100 people.This research method uses quantitative research. Data collection techniques are carried out by making observations with questionnaire media. The data analysis method used multiple linear regression. The data is processed by SPSS software. Results of the study showed that all hypothesis can be accepted, in which all variables all influence positively. From the results it can be concluded all the variables have implications for the effect of the positive to support the performance of employees at PT BCA Life Insurance (BCA Life) which meansthat the companyis getting better at motivating employees and The support to theenvironmental work that is conducive in the direct performance of employees will increase.Keyword : Motivation, Work Environment, and Employee Performance